Diet preference with regional variation of body mass index and hand grip strength of Indian females - Varte, Lalhmunlien Robert; Rawat, Shweta; Singh, Inderjeet; Pal, Madhu Sudan; Majumdar, Dhurjati (Asian Journal of Medical Sciences, 2013)
Introduction: Nutritional content of diet of vegetarian and non-vegetarian differs in terms of food composition and vegetarian diets are often low in protein, probably causing a difference in body composition, structure and strength characteristics. Purpose of study: To study anthropometric, body composition and hand strength differences among 641 vegetarian and 424 non-vegetarian Indian women, aged 20–60 yrs. Methods: ANOVA, t-test, multivariable stepwise regression and logistic regressions were performed to analyse association between BMI, hand grip strength and potential confounders using SPSS Version 17 for Windows. p < 0.05 referred to as statistically significant. Results: Vegetarians had less body fat than non-vegetarians. Statistically significant difference was found in their grip strength (GS) (t = 2.459, p < 0.05) and BMI (t = 2.188, p < 0.05). Height and weight were positively associated with grip strength in the vegetarian group while height and fat free mass were seen to be positively associated with grip strength in the non-vegetarian group. Grip strength was greater in non-vegetarian group and the vegetarians had lower BMI (25.33 kg/mt2 ± 4.56) than nonvegetarians (25.95 kg/mt2 ± 4.45, t-test = 2.188, p<0.05). Conclusion: Those with greater grip strength (non-vegetarian group) had greater chance of being obese than those with lower grip strength (vegetarian group). (OR = 2.609, 95% CI 1.487 - 4.577). However, lower levels of body mass indices of the vegetarian women suggest that they are healthier than non-vegetarians in terms of BMI. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8096 Asian Journal of Medical Sciences 4(2013) 43-51